PI SZ phenotype in chronic obstructive pulmonary disease. Issue 7 (July 1997) - Alvarez-Granda, L; Cabero-Perez, M J; Bustamante-Ruiz, A; Gonzalez-Lamuño, D; Delgado-Rodriguez, M; García-Fuentes, M
Abstract : BACKGROUND: A study was undertaken to clarify whether the PI SZ phenotype of the protease inhibitor system predisposes to chronic obstructive pulmonary disease (COPD). METHODS: The prevalence of PI Z and PI SZ deficient phenotypes was investigated in a population of 702 patients with COPD followed up at the Chest Unit of a tertiary hospital and in 15400 newborn infants from the same geographical area. Individuals with deficiency were detected by screening of dried blood spots on filter paper using a comparative electro-immunodiffusion technique for alpha 1-antitrypsin and transferrin. The serum phenotype was confirmed by means of isoelectrofocusing on polyacrylamide gel. RESULTS: Of the 702 blood samples from patients with COPD, six PI Z subjects (0.85%) and one PI SZ (0.14%) were detected. Of the 15400 samples from neonates, the number of PI Z subjects was eight (0.052%) and that of PI SZ was 24 (0.156%). The difference between the two groups was significant for PI Z but not for PI SZ. CONCLUSIONS: The data do not indicate an increased risk for development of COPD associated with the PI SZ phenotype but confirm the predisposition of PI Z individuals for the development of COPD.